2015
DOI: 10.1088/2040-8978/17/11/114015
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable plasmonic substrate with tunable resonances for surface-enhanced Raman spectroscopy

Abstract: Transparent and flexible functional nanostructures are very important for flexible electronic devices, such as roll-up displays, handheld portable devices, and wearable electronics, and have attracted growing scientific and industrial interest in recent years. We produced a facile and flexible hybrid structure by conjugating plasmonic nanostructures onto the surface of a poly (dimethylsiloxane) (PDMS) elastomer. Such flexible hybrids were able to remarkably enhance Raman scattering from small molecules. Most i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…The SERS substrate on glass was immersed into an ethanol solution of 4-MBT (1 M) and left undisturbed for 8 h, followed by rinsing with copious amount of ethanol and DI water to remove the excessive 4-MBT molecules [ 12 ]. Finally, the substrate was blown dry by nitrogen before the Raman measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The SERS substrate on glass was immersed into an ethanol solution of 4-MBT (1 M) and left undisturbed for 8 h, followed by rinsing with copious amount of ethanol and DI water to remove the excessive 4-MBT molecules [ 12 ]. Finally, the substrate was blown dry by nitrogen before the Raman measurements.…”
Section: Methodsmentioning
confidence: 99%
“…After carefully adjusting the experiment conditions, we found that a 6-h immersion of the thiol-functionalized glass substrate into the nanorod aqueous solution can give optimum distributions of the nanorods onto the glass substrate. The 4-MBT was selected as probe molecules for evaluating the Raman enhancement factor (EF) of the SERS substrate, which can be adsorbed onto the gold surface to form a well-defined monolayer via its thiol group [12]. One advantage of the 4-MBT molecules as SERS probe molecules is that they exhibit clear molecular fingerprints in 400-2000 cm -1 spectral region, which can help for precisely calculating the Raman enhancement factor of a SERS substrate.…”
Section: Resultsmentioning
confidence: 99%
“…The Au nanorods (Au NRs) used in this study were synthesized using the seed-mediated growth method, which has been reported in our previous work [ 14 , 28 ]. Scanning electron microscopy (SEM) images confirm that large-area uniform Au NRs were obtained on the glass sheets for SERS ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…Au NRs were synthesized by seed-mediated growth method, which has been reported in our previous work [ 14 , 28 ]. The ice-cold NaBH 4 aqueous solution (600 µL, 0.1 M) was rapidly prepared and added into the HAuCl 4 (250 µL, 10 mM) and CTAB (9.75 mL, 0.1 M) aqueous mixture.…”
Section: Methodsmentioning
confidence: 99%